The concept of permanent establishment in the insurance business - Frescurato, Daniele (Kluwer Law International B.V., 2021)
This book focuses on the issues that the insurance companies encounter concerning a permanent establishment (PE), providing an analysis of how the concept is applied in the context of the insurance industry and further considering potential changes to the PE definition contained in tax treaties to reflect specific features of this industry. The models commonly used to negotiate bilateral tax treaties say very little about the insurance industry and how the dependent agent PE provision may affect cross-border marketing, promotion, and insurance distribution. The study furnishes an analytical framework of the insurance industry (particularly, its regulatory landscape and value chain) and advances to discuss the following aspects systematically: Comprehensive analysis of the dependent agent PE provision as laid down in model tax treaties and related commentaries; Assessment of the existence of a dependent agent PE in the context of the most common business models adopted by insurance companies; and Comparative analysis of double tax treaty policies adopted in several countries for the PE provision in the insurance business, highlighting Switzerland for comparative purposes. The author concludes by proposing changes to the definition of the dependent agent PE currently enshrined in the model treaties and their respective commentaries tailored to how insurance companies conduct their business in countries other than incorporation.